Efectiveness Comparison of Overtime Hours with Technical and Economical Employment on 10165 Ton Gwt Tanker Ship Repairation - Bimantara Panji Saputra; Fahmy Ardhiansyah; Soffiana Agustin (Indonesian Vocational Research Journal, 2022)
Aspects of ship repair planning must be considered, especially during the ship repair process. This component is closely related to what is needed by professionals in specific fields. Project completion time can also be estimated using the number of workers involved in the production process. The salary paid by the company also correlates with the number of employees. One of the techniques to speed up work on a tanker repair project by increasing working hours which is often referred to as overtime hours with two approaches to speeding up work on a project evaluated technically and economically compared by researchers. Researchers evaluate project work and calculate the workforce involved in tanker repair. Researchers perform calculations for each part of the workforce in the ship repairment process, and also analyze the scheduling of each part of the workers that have been prepared by the company. Working on the project experienced a shortage of manpower and more often used the overtime system. and it can be seen from the results of the study that adding labor is more efficient from an economic point of view because the costs incurred are less and the processing time does not exceed the specified duration. Keywords: Tanker Ships; Labor; Duration; Cost